PD‐L1 (SP142) expression in neoplastic cells predicts a poor prognosis for patients with intravascular large B‐cell lymphoma treated with rituximab‐based multi‐agent chemotherapy - Yuka Suzuki; Kei Kohno; Kosei Matsue; Ayako Sakakibara; Eri Ishikawa; Satoko Shimada; Kazuyuki Shimada; Seiyo Mabuchi; Taishi Takahara; Seiichi Kato; Shigeo Nakamura; Akira Satou (Cancer Medicine, 2020)
Abstract Background Intravascular large B‐cell lymphoma (IVLBCL) is a rare form of diffuse large B‐cell lymphoma (DLBCL) arising in extranodal sites. PD‐L1 expression of tumor cells has been reported in IVLBCL cells, but its clinicopathological relevance remains to be elucidated. Aims This study was aimed to reveal the characteristics of PD‐L1+ IVLBCL. Methods and results Neoplastic PD‐L1 expression was examined in 34 cases of IVLBCL and clinicopathological characteristics between patients with PD‐L1+ and PD‐L1− IVLBCL were compared. We assessed PD‐L1 expression with SP142 antibody. Twelve (35%) of 34 cases showed positivity for PD‐L1. The PD‐L1+ group had significantly lower survival rates compared to the PD‐L1− group. The PD‐L1+ IVLBCL group also had a significantly lower age distribution and a lower frequency of patients older than 60 years compared to the PD‐L1− group. Very recently, we speculate that there is possible link between PD‐L1+ IVLBCL and PD‐L1+ extranodal DLBCL‐NOS (eDLBCL) because features of the two groups showed overlapping. Therefore, we compared the clinicopathological characteristics of the PD‐L1+ IVLBCL and PD‐L1+ eDLBCL. There were no significant differences in clinicopathological parameters and prognosis. Conclusion The worse prognosis of the PD‐L1+ group might be caused by immune evasion mechanisms, which are linked to PD‐L1 expression. Therefore, PD‐L1+ IVLBCL cases might be regarded as good candidates for targeted immunotherapy. We also highlighted the overlapping features of PD‐L1+ IVLBCL and PD‐L1+ eDLBCL. This result suggests that they should be regarded as one entity, immune evasion‐related extranodal large B‐cell lymphoma.